Ethos : Jurnal penelitian dan pengabdian - Universitas Islam Bandung. Pusat Pengembangan Teknologi dan Lingkungan Hidup (Pusat Penerbitan Universitas (P2U), Lembaga Pengabdian Pada Masyarakat, Universitas Islam Bandung, 2003)
Scientific journal dedicated as a media for a scientific study of the results of research and studies on the critical analysis of contemporary development issues.
Keywords: Science : Periodicals; Technology : Indonesia : Periodicals; Social sciences : Periodicals; Science; Social sciences; Technology; Indonesia